Morphological survival and subsequent in vitro maturation of denuded and cumulus compact Bubaline oocytes cryopreserved by ultra rapid cooling - Purohit, Govind Narayan; Meena, Vinoj; Solanki, Kanika (Journal of Buffalo Science, 2012)
Culturable grade oocytes (n=380) recovered by aspiration of surface follicles from buffalo ovaries (n=97) were either mechanically denuded (DN) or kept cumulus compact (CC) and were vitrified in Dulbecco’s phosphate buffered saline + 0.4% sucrose, 0.4% bovine serum albumin and 6 M concentrations of either ethylene glycol (EG) or propylene glycol (PG). Oocytes were randomly allocated to four groups of vitrification (EGCC, EGDN, PGCC and PGDN) and cryostorage for 7-10 days in liquid nitrogen. They were then warmed to record morphological survival and morphologically normal oocytes were matured in vitro along with fresh oocytes (control) for 24 h in TCM-199 containing hormones (LH + FSH + estradiol) at 38.5 0C and 5% CO2 in humidified air in a CO2 incubator. The arcsine transformed data of the proportion of morphologic survival of oocytes and in vitro maturation of oocytes was compared by DNMR-test. The morphologically normal oocytes were significantly higher (P<0.05) for cumulus compact oocytes compared with denuded oocytes for both cryoprotectants EG and PG. The in vitro maturation was significantly higher (P<0.05) for non-vitrified oocytes (control) compared to vitrified oocytes. Significantly higher (P<0.05) proportion of cumulus compact oocytes matured in vitro compared to denuded oocytes for both cryoprotectants EG and PG. The differences between the cryoprotectants were non-significant. It was concluded that cryo-damage to the oocytes during vitrification can be minimized by the presence of cumulus cells with the oocyte, whereas the two cryoprotectants EG and PG are equally effective in preventing cryodamage to oocytes.